Niño indices for two types of ENSO - Ren, Hong-Li; Jin, Fei-Fei (Geophysical research letters, 2011)
El Niño‐Southern Oscillation (ENSO), which dominates variability on interannual timescale in the climate system, is known to exhibit various spatio‐temporal characteristics. Recent studies show that in additional to a canonical El Niño with its major center of sea surface temperatures (SST) anomalies in the equatorial Pacific cold‐tongue region, a different type of El Niño with its major action center shifted to the warm‐pool edge has emerged and become more common during the past two decades. Because the SST patterns of these two types of El Niño events are highly correlated, neither of the traditional Niño3 and Niño4 SST indices alone is effective in representing the new‐type El Niño. Through a simple transformation of the Niño3 and Niño4 indices, we devised two new indices that separately identify the two types of ENSO events. Unlike the Niño3 and Niño4 indices, the two new indices are of little simultaneous correlation. The SST patterns associated with these new indices capture SST characteristics of the two types of ENSO. Their running lagged‐correlations capture different ENSO‐phase propagations and ENSO regime changes associated with the climate shift in 1976/77.